Analysis of bycatch in the South African midwater trawl fishery for horse mackerel Trachurus capensis based on observer data - Reed, JR; Kerwath, SE; Attwood, CG (African journal of marine science, 2017)
The South African midwater trawl fishery targets adult horse mackerel Trachurus capensis. The bulk of the catch is taken by a single freezer-trawler, the biggest fishing vessel operating in South African waters. As fishing takes place off the south coast in ecologically sensitive areas, there are concerns about the potential impacts of this fishing operation on non-target species. Fishing behaviour and bycatch of this fishery from 2004 to 2014 were investigated by analysing observer records with regard to catch composition, volume and temporal and spatial patterns. The midwater trawl fishery was estimated to have caught 25 415 tonnes annually, with a bycatch of 6.9% of the total catch, by weight. There are species overlaps with various fisheries, namely the demersal trawl, small-pelagic, line, shark longline and squid fisheries, yet the total bycatch estimates from this fishery are generally small relative to catches taken in the target fisheries. Bycatch species with the highest average annual catches were chub mackerel Scomber japonicus, redeye roundherring Etrumeus whiteheadi, ribbonfish Lepidopus caudatus and hake Merluccius spp. Large-fauna bycatch species included sunfish Mola mola as well as a number of CITES II- and IUCN-listed species, such as Cape fur seal Arctocephalus pusillus, dusky shark Carcharhinus obscurus, smooth hammerhead shark Sphyrna zygaena and thresher sharks Alopias spp. The 97.9% observer coverage is high and the 6.9% bycatch rate low compared to other South African fisheries; however, due to the large size of the individual hauls (average of 46.3 t), the average sampling rate of 1.56% is low. Our analyses suggest that bycatch in the South African midwater trawl fishery has been lower than in other South African fisheries and similar fisheries elsewhere, but due to the combination of high catch volumes and low sampling rates, estimation errors for rare species are high and there is a substantial risk of incidental unmonitored bycatch of rare large fauna and aggregations of small fauna. This could be mitigated by spatio-temporal management of this fishery, to avoid fishing in high-risk areas, and the introduction of an electronic monitoring programme.